Use of the oxygen reserve index/FiO2 as a non-invasive index to estimate venous admixture in anesthetized dogs - Bellini, Luca; Maney, Jill K.; Zanusso, Francesca; Dzikiti, Brighton T. (Frontiers in Veterinary Science, 2025)
The oxygen reserve index (ORi) is a novel, non-invasive parameter that estimates arterial oxygen partial pressure (PaO2) during hyperoxia when the fraction of inspired oxygen (FiO2) is elevated. This study aimed to assess the utility of the ORi/FiO2 ratio as an index for quantifying F-shunt, serving as an estimate of venous admixture. Anesthetic records were reviewed from 44 dogs undergoing general anesthesia and requiring arterial catheterization. ORi was measured via a CO-oximeter using a probe on the tongue. Paired measurements of PaO2, obtained by blood gas analysis, and ORi were taken at various FiO2 levels to achieve an ORi between 0 and 1. Venous admixture was quantified by F-shunt. Spearman’s correlation coefficient assessed the relationship between ORi/FiO2 and F-shunt. Youden’s index identified the optimal cut-off point to predict a physiological F-shunt (≤ 10%). A total of 77 paired observations were collected, revealing a moderate negative correlation between F-shunt and ORi/FiO2 (rho = −0.59, p < 0.001). An ORi/FiO2 cut-off of 1.2 demonstrated 80% sensitivity for identifying dogs with an F-shunt ≤10%, with a ROC curve area above 80%. However, the index was less effective at distinguishing dogs with higher shunt fractions. The ORi/FiO2 index identifies dogs with low F-shunt during anesthesia with strong sensitivity and predictive accuracy, potentially ruling out the occurrence of ventilation-perfusion inequality. However, it cannot replace blood gas analysis for quantifying venous admixture.